The application of the Layer of Protection Analysis (LOPA) in Sour Water Refinery Process - Ehsanollah Habibi; Saeed Zare; Mehrzad Keshavarzi; Maryam Mousavi; Hossein Ali Yousefi (International Journal of Environmental Health Engineering, 2013)
Aims: The objective of this study was to analyze major accidents take place in sour water refineries, and to assess the adequacy of safeguard layers in the system. Also it has been provided safety recommendations in regarding to our analysis. Materials and Methods: Using the layer of protection analysis (LOPA), the role of protective layers in controlling the potential risks in Sour Water Recycling Unit is determined and required recommendations to reduce risk are provided. Results: This study showed that there are 49 high risk areas in Sour Water Recycling Unit. Moreover, Excessive flow rate in pipelines, Excessive temperature, Reverse flow, H 2 S leakage, Flow interruption, and Corrosion are the main identified hazards. Conclusion: It can be conclude that the effectiveness of protective layers is not enough and additional protective layers are required to improve the process safety system. Furthermore, LOPA is an improved technique when use the output of hazard and operability study (HAZOP) and it has some advantages due to its semi-quantitative nature in estimating hazards.